2007
DOI: 10.1111/j.1553-2712.2007.tb01864.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Triage Liaison Physician on Emergency Department Overcrowding and Throughput: A Randomized Controlled Trial

Abstract: A TLP improved important outcomes in an overcrowded ED and could improve delivery of emergency medical care in similar tertiary care EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
73
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 17 publications
4
73
0
4
Order By: Relevance
“…It is a single-center study, and one of two randomized control trials [20]. To increase its generalizability from academic tertiary level centers, a multi-center trial is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a single-center study, and one of two randomized control trials [20]. To increase its generalizability from academic tertiary level centers, a multi-center trial is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Its role is to interact and start interventions on patients without an ED care space after interacting with the triage nurse. At least 10 studies testing the impact of adding a physician to the existing nurse at triage have shown some benefit [17-26] but only one of these was a randomized trial [20]. We modified an Australian model of physician-triage and report the evaluation of a MDRNSTAT.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency department (ED) crowding, in which patient care cannot be provided within a reasonable time due to excess demand for emergency services, is a serious and challenging problem [1], [2]. In Japan, 13,100 patients in critical condition experienced an ambulance diversion more than four times during one ambulance transportation; about 21% of these ambulance diversions were caused by ED crowding [3].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study using this same model [12] there was improvement in time to physician evaluation and reduction in length of stay (LOS) and time on diversion following the addition of a physician in triage. In three similar models to the research site, Han et al [4] , Partovi et al [5] , and Holroyd et al [6] showed a reduction in overall LOS and number of patients leaving without being seen (LWBS). In two studies from the United Kingdom, Terris et al [7] noted a reduction in number of patients waiting to be seen at any one time utilizing a physician in triage while Subash et al [10] showed that team triage for three hours a day reduced time to see a doctor and time to radiology during the time of intervention but not for the remainder of the day.…”
Section: Discussionmentioning
confidence: 99%
“…studies in the literature that have investigated the use of a physician in triage [4][5][6][7][8][9][10][11][12] . The majority of these studies have focused on patient flow metrics for measured outcomes.…”
mentioning
confidence: 99%